A novel design approach: increase in storage and transport efficiency for liquid hydrogen by using a dual concept involving a steel-fiber composite tank and thermal sprayed insulating coatings - Hauer, Michél; Schmidt, Stefan; Gericke, Andreas; Brätz, Oliver; Möhrke, Lukas; Biswal, Pratidhwani; Stroetmann, Nicco; Henkel, Knuth-Michael (Frontiers in Energy Research, 2024)
Wind power-to-gas concepts have a high potential to sustainably cover the increasing demand for hydrogen as an energy carrier and raw material, as it has been shown in the past that there is an enormous potential in energy overproduction, which currently remains unused due to the shutdown of wind turbines. Thus, there is barely experience in maritime production, offshore storage, and transport of large quantities of liquid hydrogen (LH2) due to the developing market. Instead, tank designs refer to heavy standard onshore storage and transport applications with vacuum insulated double wall hulls made from austenitic stainless steel and comparatively high thermal diffusivity and conductivity. This reduces cost effectiveness due to inevitable boil-off and disregards some other requirements such as mechanical and cyclic strength and high corrosion resistance. Hence, new concepts for LH2 tanks are required for addressing these issues. Two innovative technical concepts from space travel and high-temperature applications were adopted, combined and qualified for use in the wind-power-to-gas scenario. The focus was particularly on the high requirements for transport weight, insulation and cryogenic durability. The first concept part consisted of the implementation of FRP (fiber-reinforced plastics)–steel hybrid tanks which have a high potential as a hull for LH2 tanks. However, these hybrid tanks are currently only used in the space sector. Questions still arise regarding interactions with coatings, production, material, temperature resilience and design for commercial use. Thermally sprayed thermal barrier coatings (TBC) in turn show promising potential for surfaces subject to high thermal and mechanical stress. However, the application is currently limited to use at high temperatures and needed to be extended to the cryogenic temperature range. The research on this second part of the concept thus focused on the validation of standard MCrAlY alloys and innovative (partially) amorphous metal coatings with regard to mechanical-technological and insulating properties in the low temperature range. This article gives an overview regarding the achieved results including manufacturing and measurements on a small tank demonstrator.